Parasympathetic Nerve Functions in Type 2 Diabetes Mellitus: Relation to Glycemic Status and Duration of Diabetes - Alam, Md Khairul; Begum, Noorzahan; Begum, Selina (Journal of Bangladesh Society of Physiologist, 2009)
Background: Cardiovascular autonomic dysfunction is associated with higher mortality and is a common health problem observed in diabetic patients. Early detection of autonomic dysfunction in diabetic patient is important for prevention of this complication. Objectives: The study has been designed to observe the parasympathetic nerve function status in type 2 diabetic subjects in order to assess the relationship between glycemic status and duration of diabetes and the parasympathetic nerve function. Study Design: This cross section study was carried out in the Department of Physiology, Bangabhandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. Forty seven type 2 diabetic subjects were included in two groups. Group B consisted of 25 recently diagnosed diabetic subjects aged 40-68 years and group C consisted of 22 subjects having duration of diabetes for 10 - 20 years. Twenty five (25) age and BMI matched healthy subjects were included in group A (non diabetic) for control. Methods: Parasympathetic nerve functions were assessed by three simple non invasive cardiovascular reflex tests. These were Valsalva maneuver, Heart rate variation (HRV) to deep breathing, HRV to standing up. Glycemic status was assessed by serum glycosylated hemoglobin (HbA1C) and fasting plasma glucose (FPG). Data were analyzed by ât' test, Pearson's correlation coefficient. Results: Valsalva ratio was significantly lower in group C than that of group A but no significant difference was observed between group B & A and also between B and C. HRV in deep breathing and 30th:15th ratios were significantly lower in both the diabetic groups B and C than those of group A but these values were semilar in group B and C. Values of correlation of fasting plasma glucose with valsalva ratio, HRV in deep breathing and 30th:15th ratios in standing test in all three groups were not statistically significant. But correlation of duration of diabeties with valsalva ratio was stastically significant but with RHV in deep breathing and 30th:15th ratios were not significant. Conclusion: From this study it may be concluded that there was progressive deterioration of parasympathetic function with increase in duration of diabetes in patients suffering from type 2 diabetes. Key Words: Parasympathetic, Nerve, Diabetes, Neuropathy Â doi: 10.3329/jbsp.v3i0.1793 Â J Bangladesh Soc Physiol.2008 Dec;(3):42-49.